Adherence to botulinum toxin therapy in female patients with idiopathic overactive bladder: a 48-month real-world observational study : urology - Nestler, Sebastian; Grüne, Britta; Schilchegger, Lydia; Neisius, Andreas (International urology and nephrology, 2025)
Purpose To evaluate therapy adherence rates in female patients with idiopathic overactive bladder (iOAB) undergoing therapy with 100AE botulinum toxin A over a 4-year follow-up period. Methods All female patients who received their first intravesical injection of 100AE botulinum toxin A for iOAB at a single centre between January 2018 and December 2020 were evaluated over a 48-month follow-up for treatment benefit, reduction of urgency incontinence episodes, bladder capacity, repeat injections, adverse events, adherence to therapy, and reasons for discontinuation. Results A total of 106 women met our inclusion criteria and 15 were excluded. Of the remaining 91 women, the mean age before the first injection was 64 years and the median urinary incontinence episodes (UIE) was 3.6. After 48 months, 64 patients (70.3%) continued the therapy. Bladder capacity increased by a median of 105-207 cc and the UIE was reduced by 2.64 episodes daily. Complete continence was achieved in 31 patients (34.1%). After the second cycle, 71 patients (78.0%) were satisfied with therapy, with similar results in subsequent cycles. In addition, most patients who adhered to the therapy received four or five rounds of treatments. Adverse events were mainly urinary tract infections (11.8%) in the first cycle and less in subsequent cycles. No de novo clean intermittent self-catheterisation was detected. The reasons for discontinuation among the 27 patients who discontinued therapy were diverse and mostly unmet expectations. Conclusions Female patients with iOAB had good therapy adherence to botulinum toxin A, evidenced by stable improvements in UIE and bladder capacity and high rates of satisfaction in patients’ self-assessment.
Gesehen am 23.06.2025